2020
DOI: 10.1021/acs.molpharmaceut.0c00668
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bile Composition on Membrane Incorporation of Transient Permeability Enhancers

Abstract: Transient permeability enhancers (PEs), such as caprylate, caprate, and salcaprozate sodium (SNAC), improve the bioavailability of poorly permeable macromolecular drugs. However, the effects are variable across individuals and classes of macromolecular drugs and biologics. Here, we examined the influence of bile compositions on the ability of membrane incorporation of three transient PEs—caprylate, caprate, and SNAC—using coarse-grained molecular dynamics (CG-MD). The availability of free PE monomers, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 70 publications
1
48
0
Order By: Relevance
“…Methanol [274,413,414], Ethanol [149,242,284,387,[414][415][416][417][418][419][420], Propanol [414,421], Isopropanol [284], Buthanol [414,417,422], Caprate [423], Glycerol [424], Isopropanol [416],…”
Section: Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methanol [274,413,414], Ethanol [149,242,284,387,[414][415][416][417][418][419][420], Propanol [414,421], Isopropanol [284], Buthanol [414,417,422], Caprate [423], Glycerol [424], Isopropanol [416],…”
Section: Antioxidantsmentioning
confidence: 99%
“…Thymol [425] Natural polymers Lignin [426][427][428], Polyphenols [429], Cellulose [430,431], Polysialic acid [432] Gabaergic ketones Carvone, Menthone, Pulegone, Dihydrocarvone, Thujone [433] Taste and aroma Menthol [342,434], Terpenoids [435], Coumarin [132,284,436,437], Limonene [132], 4-ethylphenol (wine/beer aroma) [406], Tannins (wine) [438], Catechin [282] Caffeine and its derivatives Caffeine [132,439], Rosmarinic acid [440][441][442], Caffeic acid [441,443], Chlorogenic acid [441], Paraxanthine [132], Caffeic acid derivatives [444] Pigments Violacein [445,446], Marennine [447] Bile salts [280,423,448] Steroids Betulin [449], Saponins [450,451], Glycyrrhizic acid (saponin) [252,452,453], Withaferin-A and Withanone [454] Lipids N-arachidonylglycine and oleoyl-L-carnitine [137]...…”
Section: Antioxidantsmentioning
confidence: 99%
“…The exact mechanism of this interaction is not clear, but it is expected that colloidal rearrangement alters the exchange of lipid monomers between the adsorbed membrane and the lipid colloids solubilized within the aqueous media. 51 …”
Section: Resultsmentioning
confidence: 99%
“…This dynamic equilibrium is expected to be dependent on lipolysis kinetics and colloidal self-assembly because changes in the composition and structure of lipid colloids alter the expulsion dynamics of individual lipid monomers. 51 …”
Section: Resultsmentioning
confidence: 99%
“…Studies using Caco-2 monolayers also indicated that C 8 is far less efficacious as a PE for paracellular marker molecules compared to C 10 [42]. The low efficacy and potency of C 8 are likely due to its reduced propensity to partition into enterocyte plasma membrane lipid bilayers compared to C 10 [43]. There is a counter-argument offered to suggest that C 8 may be effective as a PE because its higher critical micellar concentration (CMC) favors the presence of high concentrations of the active monomeric form in the GI lumen compared to longer chain fatty acids.…”
Section: The Transient Permeation Enhancer ® (Tpe ® ) Technologymentioning
confidence: 99%